Residual Analysis and Tidal Harmonic Components in Bangkalan Regency, East Java - Prayogo, Luhur Moekti; Yuliardi, Amir Yarkhasy; Spanton M, Perdana Ixbal; Suwarsih; Joesidawati, Marita Ika; Sukma, Raka Nur (MIYANG, 2023)
Bangkalan Regency is one of Madura, East Java, where some of its areas are located in a coastal environment. The coastal environment can experience economic development due to the transportation aspect so that many industries have been established in that environment. Studies on oceanographic parameters are essential because management of coastal environments can not be separated from oceanographic information: The tides information about the tidal characteristics can be obtained after performing a harmonic analysis, which produces the value of harmonic components. This study analyses the residue and tidal harmonic components using the LP-Tides Matlab software in the Sepulu district, Bangkalan Regency, East Java. The data used are January 2021 data from the Geospatial Information Agency. This research shows that the main harmonic components generated include K2, M4, MS4, M2, S2, N2, K1, O1, and P1. The tidal type shows that the Sepulu district is a semi-diurnal type with a Formzahl number = 0.08566. The maximum observation and prediction data values for January 2021 in the Sepulu district are 978 and 1273.64 mm. The MSL value is 434 mm, with an average tidal residue value between the observation and predictive data = 166.01 mm. Then the calculation of the RMSE value and standard deviations are 12.88 and 125.90 mm